Differentiation of fractionated components of lard from other animal fats using different analytical techniques - Marikkar, Mohammed Nazrim; Ahmad Nizar, Nina Naquiah; Mirghani, Mohamed Elwathig Saeed; Ahmad Fadzillah, Nurulhidayah; Abdul Manaf, Yanty Noorzianna (Penerbit UKM, 2017)
A study was conducted to differentiate fractionated components of lard namely lard olein (LO) and lard stearin (LS) from other common animal fats. Lard fractions and animal fats were analyzed using differential scanning calorimetry (DSC), elemental analyzer–isotope ratio mass spectrometry (EA-IRMS), gas chromatography mass spectrometry (GC-MS), and Fourier transform infrared spectroscopy (FTIR). Overlay of FTIR spectra did not help to pinpoint any characteristic feature to distinguish either LO or LS from other animal fats, but overlay of DSC cooling curves helped a successful discrimination. The determination of δ13C from EA-IRMS showed that the values corresponding to the fractionated components of lard were significantly (p<0.05) different from those of the other common animal fats.GC-MS analysis showed that direct comparison of overall fatty acid data was not able to discriminate LO and LS from other animal fats, but the application of principal component analysis (PCA) to fatty acid data helped a successful discrimination.